2005
DOI: 10.2355/isijinternational.45.538
|View full text |Cite
|
Sign up to set email alerts
|

Design of Bed Structure Aiming the Control of Void Structure Formed in the Sinter Cake

Abstract: Fig. 12.Comparison of computed temperature profiles at the center, TC C , and the surface, TC O , of the pellets of 5, 10, 15 mm in size during sintering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 5 publications
0
49
0
Order By: Relevance
“…[18][19][20] Similar process named mosaic embedding iron ore sintering (MEBIOS) displays its predominance on efficiently using low-grade iron ores and limonite, ensuring high productivity and reducibility and enhancing sinter strength. [21][22][23] Our previous study 24) showed that acidic sinter (basicity < 0.5) made from titanomagntite concentrate mainly solidifies in the form of titanohematite and titanomagnetite and very few perovskite was generated in this sinter. Ultra-high basicity (basicity > 2.5) facilitated the formation of SFCA in sinter, which can offset the adverse effect of perovskite to sinter strength due to its excellent bonding strength.…”
Section: Preparation Of Bf Burden From Titanomagnetite Concentrate Bymentioning
confidence: 99%
“…[18][19][20] Similar process named mosaic embedding iron ore sintering (MEBIOS) displays its predominance on efficiently using low-grade iron ores and limonite, ensuring high productivity and reducibility and enhancing sinter strength. [21][22][23] Our previous study 24) showed that acidic sinter (basicity < 0.5) made from titanomagntite concentrate mainly solidifies in the form of titanohematite and titanomagnetite and very few perovskite was generated in this sinter. Ultra-high basicity (basicity > 2.5) facilitated the formation of SFCA in sinter, which can offset the adverse effect of perovskite to sinter strength due to its excellent bonding strength.…”
Section: Preparation Of Bf Burden From Titanomagnetite Concentrate Bymentioning
confidence: 99%
“…Accordingly, the reduction degradation properties are increased by promoting the formation of iron oxide minerals by reducing the slag content and by blending in large amounts of limonite-based minerals with favorable sinter reaction properties and dispersing them into the hematite mineral texture. However, it is thought that the reaction participation of FeO components that results from the addition of MgO components and strengthening of the reducing atmosphere promotes the formation of FeO · Fe 2 ing assimilation process, and evaluation of local strains in the resulting iron oxide [Sasaki] Limonite-based ores characteristically contain combined water and large numbers of pores in their original form, and subjecting them to thermal processing results in a highly reactive material with cracks (low strength) and pores (micropores). When an iron ore of this type is blended in large quantities in the sinter production, the assimilation reaction of the iron ore particles with the resulting melt is naturally speeded up, making it more receptive to processes such as the formation of pores and micro-pores, which has a large effect on the cold strength.…”
Section: Basic Research Intomentioning
confidence: 99%
“…However, there are still many issues requiring further study, including consideration of the reduction and oxidation reactions that occur in the firing cured bed in cases where coke powder is added to the pellets, for example, and methods for generating meshes for suitably expressing contraction of the bed height or changes in the bed structure caused by the flow of 2) melt occurring in the solid phase. From a heat transfer study by Kasai et al 2) and a model study by Otomo,11) it was judged that the diameter of the dense and large spheres should preferably be about 10-15 mm.…”
Section: Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Segregation control is one such technology. 11,18,19) The hightemperature hold time tends to be short in the upper layer of the sinter bed, while the peak temperature of the lower layer is prone to be too high. Segregating coke particles into the top surface moderates the temperature at all layers and improves the quality of the sinter.…”
Section: Introductionmentioning
confidence: 99%